Dielectric Behaviour of Binary Mixture of Diethylene Triamine with 2-Ethoxy Ethanol - Kalamse, G.M.; Pande, Rekha; Nimkar, M.J. (Asian Journal of Chemistry, 2016)
Densities, viscosities, refractive indices, dielectric constant (e') and dielectric loss (e") of 2-ethoxy ethanol, diethylene triamine and their mixtures for different mole fractions of diethylene triamine have been measured at 10.7 GHz microwave frequency. The values of dielectric parameters (e' and e") have been used to evaluate the molar polarization, apparent polarization and the excess permittivities. Excess refractive index, viscosity and activation energy of viscous flow have also been estimated. These parameters have been used to explain the formation of complexes in the system. The excess values have been fitted through least squares with all points equally weighted by using the Redlich-Kister equation, to estimate the binary coefficient and standard deviations (s).